Shifting tax burdens through exemptions and evasion an empirical investigation of Uganda - Gauthier, Bernard P.; Reinikka, Ritva; World Bank. Development Research Group (Washington, D.C. : The World Bank, Development Research Group, Pu blic Services for Human Development, 2001)
Tax burdens vary for firms of different sizes due to their variable tendency to seek exemptions or evade taxes.
Title from title screen as viewed on Aug. 24, 2002.
"December 2001."
Includes bibliographical references (p. 25).
Keywords: Business enterprises -- Taxation -- Uganda; Tax exemption -- Uganda; Tax evasion -- Uganda